TAXES AND FISCAL PRESSURE IN ACAPULCO, 1777-1809 (Tzintzun, Revista de Estudios Históricos, 2016)
Taxes and Fiscal Pressure in Acapulco, 1777-1809 analyses the intricate world ofprivate local interests, the complicated government officials’ family nets and theirdeep corruption. José de Gálvez’s arrival to New Spain as a general supervisorallowed people to know about some cases of corruption like the one Viceroy Marquisde Cruillas was involved in through his nephew Fernando de Monserrat, governorof Acapulco, who was benefited by commercial activities without paying taxes or byillegal trade. From that moment on Gálvez finished the Viceroy’s corrupted careerand he started drastic political and administrative innovations. He ordered traderegulations with Asia be applied, He punished the Authorities involved inmisconduct and he took measures to stop fraud against the Royal Treasury Office.The article also studies the various forms of resistance that these measures brokeout, the main local outlaws and their accomplices in Mexico City
Keywords: Taxes; corruption; commercial activities; bourbon reforms; Acapulco; José de Galvez; Fernando de Monserrat